Atomic data and collisional-radiative model for beryllium and its ions - Kondratyev, D.; Vainshtein, L.; Bray, Igor; Fursa, Dmitry; Ralchenko, Y. (Institute of Physics Publishing Ltd., 2014)
In this work we present a collisional–radiative model constructed for all ionization stages of beryllium. Convergent close-coupling, K-matrix and Coulomb–Born-exchange methods were applied to calculate the necessary atomic data. For the neutral beryllium atom a comparison of all methods is given. Fractional ion abundances, radiative power losses and electron cooling rates were calculated as functions of electron temperature. The comparison with other available data shows a rather good agreement.